1983
DOI: 10.1295/polymj.15.797
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Motion in Poly(amino acid) VIII. β2-Form Crystals of Poly(D-glutamic acid)

Abstract: ABSTRACT:The {32-form crystal ofpoly(D-glutamic acid) has a strong interaction between the sheets, in which chains are bound side by side by intermolecular hydrogen bonds. In this work, the molecular motion of poly(D-glutamic acid) in the fully annealed /32-form crystal was studied. The linear thermal expansion coefficient for the intermolecular periodicity, 10-5 cc-1 ), was similar to that for the intersheet periodicity below 200°C, indicating that there is only ordinary thermal lattice vibration in the {32 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…1 The molecular motions in a number of poly(L-glutamate)s have been investigated in detail by various methods including dynamic mechanical, dielectric, and wide-line nuclear magnetic resonance measurements. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] It has been reported that glutamate side chains have motion near room temperature, accompanied by some mechanical and dielectric relaxations, while the backbone chain remains in the rigid a-helical conformation.…”
mentioning
confidence: 99%
“…1 The molecular motions in a number of poly(L-glutamate)s have been investigated in detail by various methods including dynamic mechanical, dielectric, and wide-line nuclear magnetic resonance measurements. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] It has been reported that glutamate side chains have motion near room temperature, accompanied by some mechanical and dielectric relaxations, while the backbone chain remains in the rigid a-helical conformation.…”
mentioning
confidence: 99%